2018
DOI: 10.1182/bloodadvances.2017013722
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of hematology-oncology trainees' postfellowship career pathways with a focus on nonmalignant hematology

Abstract: Nonmalignant hematologic conditions are extremely prevalent and contribute significantly to the global burden of disease. The US health care system may soon face a shortage of specialists in nonmalignant hematology. We sought to identify factors that lead hematology-oncology fellows to pursue (or not to pursue) careers in nonmalignant hematology. Cross-sectional, web-based survey distributed to 149 graduates of a hematology-oncology fellowship program at a large academic medical center between 1998 and 2016. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
(32 reference statements)
1
8
0
Order By: Relevance
“…A single-institution survey found that hematology/oncology fellows' clinical experiences during fellowship, perceptions of the intellectual stimulation of their chosen field, and having a supportive mentor have a "significant" influence on the types of patients and conditions they treat after fellowship (hematology, oncology, or both). 9 These findings are consistent with other studies that have identified mentorship and networking as critical components to career development within academic medicine. 12 Other studies have highlighted the importance of preclinical education, clinical exposure during medical school and residency, and lifestyle factors in positively and sometimes negatively motivating trainees' decisions to pursue subspecialty training at all, as well as their specialty choices.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…A single-institution survey found that hematology/oncology fellows' clinical experiences during fellowship, perceptions of the intellectual stimulation of their chosen field, and having a supportive mentor have a "significant" influence on the types of patients and conditions they treat after fellowship (hematology, oncology, or both). 9 These findings are consistent with other studies that have identified mentorship and networking as critical components to career development within academic medicine. 12 Other studies have highlighted the importance of preclinical education, clinical exposure during medical school and residency, and lifestyle factors in positively and sometimes negatively motivating trainees' decisions to pursue subspecialty training at all, as well as their specialty choices.…”
Section: Introductionsupporting
confidence: 90%
“…Our findings showing a strong statistical association between hematology mentorship experiences and fellows' plans to enter hematology-only careers align with other studies that have found that mentorship is 1 of the most important factors in fellows' specialty choices. 9,14 The strong association of research mentorship with hematology/ oncology fellows' interest in pursuing hematology-only careers may be related to the prominence of academic medicine careers in hematology. 10,24 Results of a small survey of hematology/oncology fellows trained at the National Cancer Institute-designated cancer centers demonstrated the strong emphasis on academic careers among hematology/oncology fellows, of whom 49% of those surveyed indicated that an academic career was "very important" or "extremely important."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a need for physicians with adequate training, experience, interest, and expertise in assessing and treating patients with these disorders. [1][2][3] Some hematologic issues are complex and require in-person histories and examinations, whereas others can be handled with advice electronically after a thorough chart review. 4 To improve the quality of the care provided to these patients, a virtual benign hematology consultative service was created.…”
mentioning
confidence: 99%
“…Mentorship has been demonstrated to be a critical factor associated with fellows’ plans to enter careers in classical hematology. 2 , 14 Showcasing the breadth of available mentorship signals commitment to classical hematology training and may attract applicants with diverse interests within classical hematology disciplines. Furthermore, listing additional faculty from classical hematology background in leadership may be especially important for programs with PDs whose academic interests lie exclusively in malignant hematology and/or solid tumor oncology (>80% of PDs).…”
mentioning
confidence: 99%